2019
DOI: 10.1038/s41563-019-0445-x
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired hydrophobicity promotes CO2 reduction on a Cu surface

Abstract: Aqueous electrocatalytic reduction of CO 2 into alcohol and hydrocarbon fuels presents a sustainable route towards energy-rich chemical feedstocks. Cu is the only material able to catalyse the substantial formation of multi-carbon products (C 2 /C 3), however competing proton reduction to hydrogen is an ever-present drain on selectivity. Herein, a superhydrophobic surface was generated by 1-octadecanethiol treatment of hierarchically structured Cu dendrites, inspired by the structure of gas-trapping cuticles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
627
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 638 publications
(642 citation statements)
references
References 42 publications
13
627
2
Order By: Relevance
“…[ 6–8 ] To date, many efforts have been made to achieve the production of C 1 C 3 products from CO 2 RR. [ 9–14 ] It has also been reported that C 1 products, such as carbon monoxide (CO) and formate, typically show sufficiently high activity and selectivity. [ 15–19 ] Moreover, the energy efficiencies of C 1 products should be higher than that of C 2 + products based on its mechanistic simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6–8 ] To date, many efforts have been made to achieve the production of C 1 C 3 products from CO 2 RR. [ 9–14 ] It has also been reported that C 1 products, such as carbon monoxide (CO) and formate, typically show sufficiently high activity and selectivity. [ 15–19 ] Moreover, the energy efficiencies of C 1 products should be higher than that of C 2 + products based on its mechanistic simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop efficient and highly selective catalysts, a large number of self‐supporting metal dendritic nanoarrays have been developed, including transition metals (such as Au, Ag, Cu, Bi, and Zn) and their composites. The electrodeposited Cu dendrites mainly brought forth multielectron products, including C 2 H 4 67,68,72,77 and CH 3 CHO 76. Especially, this kind of CO 2 RR electrocatalysts could even generate a remarkable ≈170 mA cm −2 current density, which might meet the commercial standard.…”
Section: Metal Nanoarrays On Conductive Substratementioning
confidence: 99%
“…Moreover, the electric field can drive almost all chemical reactions, which could be utilized as an effective method to produce the desired compounds in a controlled manner. Table 3 displays the summary of the electrodeposited metal nanodendrites as efficient CO 2 RR electrocatalysts,66–77 including, electrolyte, main product, cathode potential, current density, and Faradaic efficiency. Up till now, electrochemical deposition has been frequently adopted to prepare all kinds of self‐supported metal nanodendrite arrays as CO 2 RR electrocatalysts.…”
Section: Metal Nanoarrays On Conductive Substratementioning
confidence: 99%
See 1 more Smart Citation
“…[9] Electron and mass transfer at this interface are crucial to the electrochemical CO 2 reduction process.P revious report revealed that larger alkali cations could alter the local electric properties of electrode surface thus tuning the selectivity for CO,C 2 H 4 ,a nd C 2 H 5 OH, [10] while small organic molecule coating on the electrode surface could alter the adsorption and diffusion behaviors of CO 2 . [11] Inspired by these previous reports,h erein, we developed an artificial E/E interface enabled by quaternary ammonium cation surfactants (Figure 1). In our study,aCu-nanowire (Cu NW) electrocatalyst was used as an example to demonstrate this interface design since it has multiple reaction routes and reduction products for CO 2 RR with selectivity towards various C 1 and C 2+ products,a sw ell as the competing hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%